KAJIAN FAKTOR PENARIK (PULL FACTOR) PENGHUNI BERTEMPAT TINGGAL DI KOMUNITAS BERPAGAR (GATED COMMUNITY) STUDI KASUS KECAMATAN MEDAN SELAYANG - Giawa, Friendly C. R.; Silitonga, Shanty; Pakpahan, Raimundus (Unika Santo Thomas, 2018)
The growth of gated communities in District of Medan Selayang for 20 years is very rapid, the people today tend to choose to live in a closed community. The community considers that living in the closed and elite community is a matter of pride, even though it causes disconnection with the surrounding environment. This study aims to find out what is the pull factor of people living in gated communities, especially in Kecamatan Medan Selayang. The type of research used in the research are; Descriptive qualitative, then it is analyzed on a nominal scale and Likert Scale. This research concludes that the pull factor of residents residing in gated communities in Medan Selayang sub-district is a factor of Security, Access, Economy and Facilities, Privacy and Exclusivity.